ALQURAN TEACHING MODEL : THE EFFECT OF PROBLEM SOLVING ABILITY AND GENDER ON MATHEMATICS - Suherman Suherman; Ayu Sekarsari Suharno; Istihana Istihana (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2019)
Mathematical problem solving ability is one of the things that must be owned by students in learning mathematics. Students have low mathematical problem solving abilities caused by difficulties in solving mathematical problems that require logic. The research is aimed to determine the effect of the Alqurun Teaching Model on mathematical and gender problem solving abilities. This research is quantitative research. The population were 264 in eighth grade students of SMPN 17 Bandar Lampung. Sampling technique used by sample random sampling technique. Data analysis techniques used the normality test with Liliefors test and homogeneity test with Barlett test. Hypothesis testing using the two-way cell ANAVA test is not the same. The results showed that there was an influence of the Alqurun Teaching Model (ATM) learning model on mathematical and gender problem solving abilities. The mathematical problem solving abilities of female students are better than male students in the Alqurun Teaching Model learning.